Maternally inherited hypercholesterolemia does not modify the cardiovascular phenotype in familial hypercholesterolemia. (March 2021) - Marco-Benedí, Victoria; Laclaustra, Martín; Bea, Ana M.; Suarez-Tembra, Manuel; Plana, Núria; Pinto, Xavier; Brea, Angel; Sanchez-Hernandez, Rosa M.; Civeira, Fernando
Abstract: Background and aims: Familial hypercholesterolemia (FH) is a codominant autosomal disease characterized by a high risk of cardiovascular disease when not in lipid-lowering treatment. However, there is a large variability in the clinical presentation in heterozygous subjects (HeFH). Maternal hypercholesterolemia has been proposed as a cardiometabolic risk factor later in life. Whether this phenotype variability depends on the mother or father origin of hypercholesterolemia is unknown. The objective of this study was to analyze potential differences in anthropometry, superficial lipid deposits, comorbidities, and lipid concentrations depending on the parental origin of hypercholesterolemia within a large group of HeFH. Methods: This is a cross-sectional observational, multicenter, nation-wide study in Spain. We recruited adults with HeFH to study clinical differences according to the parental origin. Data on HeFH patients were obtained from the Dyslipidemia Registry of the Spanish Atherosclerosis Society. Results: HeFH patients were grouped in 1231 HeFH-mother-offspring aged 45.7 (16.3) years and 1174 HeFH-father-offspring aged 44.8 (16.7) years. We did not find any difference in lipid parameters (total cholesterol, triglycerides, LDLc, HDLc, and Lp(a)), nor in the comorbidities studied (cardiovascular disease prevalence, age of onset of cardiovascular disease, obesity, diabetes, and hypertension) between groups. Lipid-lowering treatment did not differ between groups. The prevalence of comorbidities did not show differences when they were studied by age groups. Conclusions: Our research with a large group of subjects with HeFH shows that a potential maternal effect is not relevant in FH. However, due to the size of our sample, potential differences between genders cannot be completely ruled out. This implies that severe maternal hypercholesterolemia during pregnancy is not associated with additional risk in the FH affected offspring. Graphical abstract: Image 1 Highlights: The clinical phenotype is highly variable among heterozygous familial hypercholesterolemia (FH) subjects. Maternal hypercholesterolemia may be associated with higher cardiometabolic risk later in life. FH is a good model to study the effect of maternal hypercholesterolemia in the offspring. We did not find any difference in heterozygous FH with maternal or paternal origin. Our results do not support any relevant effect of maternal hypercholesterolemia in the offspring.